Rumpole rests his case - Mortimer, John Clifford (New York : Viking, 2002)
A collection of short mysteries features the opinionated Horace Rumpole as he triumphs over the forces of prejudice and "muddled humanity" while tiptoeing precariously through the domestic territory of "She Who Must Be Obeyed."
Keywords: Legal stories, English; Detective and mystery fiction